Stresshanteringsprogram för långtidssjukskrivna kommunanställda kvinnor - Santell, Bo; Grossi, Giorgio (Socialmedicinsk tidskrift, 2007)
Senare års stigande sjuktal för stressrelaterad ohälsa, särskilt bland kvinnor i kommunal offentlig sektor, har aktualiserat frågan om effektiv behandling och rehabilitering av dessa tillstånd. Tjugofyra kommunanställda kvinnor, långtidssjukskrivna för stressreaktioner av Kommunhälsan i Eskilstuna, behandlades alla enligt företagshälsovårdens etablerade individuella modell. Hälften erbjöds dessutom ett externt stresshanteringsprogram i gruppform. Vid upprepade enkätundersökningar upp till ett år efter utbildningen redovisade experimentgruppen samma minskande depressionstendens men signifikant lägre grad av utmattningssyndrom jämfört med kontrollgruppen. Förbättringen återspeglades ej i biokemiska stressmarkörer. Vid en treårskontroll hade 21 procent fler bland kursdeltagarna kommit tillbaka i förvärvsarbete jämfört med kontrollerna. The aim of the study was to evaluate the effects of a stress management intervention in a sample of 24 female employees in the Swedish public sector, who were on sickleave due to stress related disorders. All parcipitants were administrated the Eskilstuna occupational health care unit´s individual treatment for stress. Half of the sample were also administered a group intervention aimed at coping with psychological/somatic symptoms of stress (experimental condition). The study design was quasi-experimental. Data were collected before and after treatment and at 6 and 12 months follow-up, by means of questionnaires and blood sampling. Rates of return to work were asessed for up to three years. Levels of depression decreased in both conditions and these improvements were maintained at follow-up. The experimental condition was superior with reference to symptoms of burnout, particularly exhaustion and the global index of the Karolinska Exhaustion Scale. Paradoxically, these improvements were accompanied by significant increases i glycated haemoglobin (HbA1C) in both groups. At three years´ follow-up 40 % in the experimenatal condition and 19 % of controls had returned to work. More studies are needed to investigate the impact of stress management interventions on physiological parameters.